Unusual synthesis of azines and their oxidative degradation to carboxylic acid using iodobenzene diacetate. Issue 4 (16th February 2018) - Sumran, Garima; Aggarwal, Ranjana; Hooda, Mona; Sanz, Dionisia; Claramunt, Rosa M.
ABSTRACT: Reaction of 3-hydrazonobutan-2-one oxime with aromatic aldehydes resulted in the formation of 1, 2-bis(arylidene)hydrazine commonly referred as azine as an unexpected product, instead of expected product 3-(aryl)methylenehydrazonobutan-2-one oxime, which were subsequently oxidized to corresponding aromatic acids with an ecofriendly oxidizing agent iodobenzene diacetate. Azines and carboxylic acids were characterized by IR and NMR ( 1 H, 13 C, HMBC, and HMQC) studies. GRAPHICAL ABSTRACT: